Application of laser scanning for monitoring condition of buildings and structures during reconstruction - Rudneva, Irina (Transfer of innovative technologies, 2021)
Ground-based laser scanning technology has been increasingly used in the last 15 years to solve problems not only in engineering geodesy, but also in the inspection of buildings and structures, in particular to identify damage and deformation during operation and reconstruction, as well as operational control of construction. and monitoring of their condition during operation, 3D-modeling of complex architectural objects. The growing popularity of laser scanning is due to a number of advantages provided by the new technology in comparison with other measurement methods. Among the advantages are the main ones: increasing the speed of work and reducing labor costs. The emergence of new more productive models of scanners, improving software capabilities allows us to hope for further expansion of the scope of ground-based laser scanning. Three-dimensional laser scanning emits millions of laser beams and, by calculating their return time, can accurately and accurately calculate their three-dimensional locations to make multiple high-speed scans combined into one system. This works by digitally recording the dimensions and spatial communication of objects by reflecting laser radiation.